2021
DOI: 10.21037/atm-21-4318
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tiRNA and tRF in APP/PS1 transgenic mice and the change of related proteins expression

Abstract: Background: Transcriptomics, such as that of non-coding RNA (ncRNA), which include microRNA (miRNA), circular RNA, and the transfer RNA (tRNA)-derived fragments (tiRNA and tRF) in Alzheimer's disease (AD) have attracted much attention recently. The tiRNA and tRFs are produced when the tRNA splits at specific sites. The expression change and related function of tiRNA and tRFs in AD has not been fully investigated.Methods: In our study, APP/PS1 transgenic mice (AD mice model) and healthy control mice were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Investigations using transgenic mice overexpressing a mutant chimeric mouse/human APP (APPswe) and a mutant human Presenilin 1 (PSEN1dE9) that develop age-dependent cognitive impairment and show abundant pathological A40-42 inclusions also identified dysregulated tRFs 69 . Lu et al, performed small RNA sequencing on hippocampal tissue from ~12-month-old male mice and identified dysregulated tRFs, validation confirmed that a tRF derived from ThrCGT was upregulated in AD mice compared to controls, whereas a tRF from LeuCAA was significantly downregulated 70 . Wu et al, found that microRNAs and tRFs were elevated in a publicly available sequencing dataset from 6 late onset AD patients and 6 age-matched healthy controls 71 .…”
Section: Alzheimer's Diseasementioning
confidence: 95%
“…Investigations using transgenic mice overexpressing a mutant chimeric mouse/human APP (APPswe) and a mutant human Presenilin 1 (PSEN1dE9) that develop age-dependent cognitive impairment and show abundant pathological A40-42 inclusions also identified dysregulated tRFs 69 . Lu et al, performed small RNA sequencing on hippocampal tissue from ~12-month-old male mice and identified dysregulated tRFs, validation confirmed that a tRF derived from ThrCGT was upregulated in AD mice compared to controls, whereas a tRF from LeuCAA was significantly downregulated 70 . Wu et al, found that microRNAs and tRFs were elevated in a publicly available sequencing dataset from 6 late onset AD patients and 6 age-matched healthy controls 71 .…”
Section: Alzheimer's Diseasementioning
confidence: 95%
“…identified 27 differentially expressed tsRNAs in the hippocampus of APP/PS1 transgenic mice and WT mice by transcriptome analysis, followed by qPCR validation of 2 tsRNAs. After bioinformatics analysis, qPCR and Western blot verification of the target genes, tRF‐Thr‐CGT‐003 and tRF‐Leu‐CAA‐004 were found to be involved in the regulation of CACNG2 and RYR1 genes related to calcium regulation 58 . Numerous studies have focused on the pathogenic role of calcium dysregulation caused by RyR channel leakage in AD 59–63 .…”
Section: Roles Of Tsrnas In the Occurrence And Development Of Central...mentioning
confidence: 99%
“…In another mechanism, downregulated 5’ tsRNA-Leu (referred to as tRF-Leu-CCA-004) was found to modulate the expression of members of the cytochrome P450 family leading to the speculation that it could affect protein expression [ 110 ]. In the archaea haloferax volcanii , the 5’ tsRNA Val (referred to as tRF-5Val) binds to the small ribosomal subunit and interferes with the peptidyl transferase, hence destabilising the growing polypeptide chain [ 28 ].…”
Section: Introductionmentioning
confidence: 99%